Optimal Approaches for Measuring Tongue-Pressure Functional Reserve - Catriona M. Steele (Journal of Aging Research)
Tongue-palate pressure is a parameter of considerable interest in the field of dysphagia. Maximum isometric tongue-palate pressures (MIPs) decline in healthy aging and in dysphagia. Functional reserve (FR) is the difference between MIPs and swallowing pressures. Reduced FR is thought to constitute a risk for developing functional swallowing impairments. We compare different approaches for calculating FR and recommend an optimal approach. Tongue-palate pressure data were collected from 78 healthy adults (40<age  40; 38>60) during anterior and posterior MIPs, regular (RESS) and effortful (ESS) saliva swallows, and water swallows (4 repetitions per task). Six different measures of reserve were calculated using maximum anterior MIPs or ESS pressures at the top, and mean or maximum RESS or water swallow pressures at the bottom of the range. Correlations with age and MIPs were explored to confirm suitability for measuring FR. The impact of normalization to maximum MIP range was explored. We conclude that an optimal measure of FR involves the comparison of maximum MIP with mean saliva swallowing pressures. This parameter declines with age, but when normalized to an individual’s MIP range, the relationship is no longer evident. This suggests that FR does not necessarily decline in healthy aging.